Experimental analysis of human lumbar vertebrae during prolonged distance driving - Amir, Muhammad Azrai; Toha, Siti Fauziah; Aris, Ishak; Md. Yusof, Hazlina (Asian Research Publishing Network (ARPN), 2016)
Back pain is commonly associated with a heavy driving or a person driving for a very long period. Inexpensive vehicles have a low system of absorbers such that the person behind the wheel and the passenger will experience pain in their back. This is mainly caused by several factors, such as the condition of the road, the performance of the absorber system of the vehicle and also the condition of the person inside the vehicle itself. This paper will discuss the factor that can be prevented and optimized to reduce whole-body vibration that might lead to fatigue.